1998
DOI: 10.1161/01.cir.98.20.2108
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor (VEGF) Expression in Human Coronary Atherosclerotic Lesions

Abstract: These results demonstrate distinct expression of VEGF and its receptors (flt-1 and Flk-1) in atherosclerotic lesions in human coronary arteries. Considering the multipotent actions of VEGF documented experimentally in vivo and in vitro, our findings suggest that VEGF may have some role in the progression of human coronary atherosclerosis, as well as in recanalization processes in obstructive coronary diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
118
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(136 citation statements)
references
References 24 publications
14
118
0
4
Order By: Relevance
“…VEGF can induce the migration and proliferation of endothelial cells and increase vascular permeability (Inoue et al, 1998). These events are consistent with the capacity to promote angiogenesis, which has a central role in cicatrization.…”
Section: Resultssupporting
confidence: 60%
“…VEGF can induce the migration and proliferation of endothelial cells and increase vascular permeability (Inoue et al, 1998). These events are consistent with the capacity to promote angiogenesis, which has a central role in cicatrization.…”
Section: Resultssupporting
confidence: 60%
“…Moreover, VEGF has been found to be upregulated in human coronary atherosclerotic lesions but not in normal coronary segments [9]. Although the mechanism by which VEGF induces plaque formation has not been established, it has been suggested that new vessel formation causes plaque progression [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains uncertain whether VEGF enhances or prevents IVD degeneration. Increased VEGF expression has been associated with the progress of atherosclerosis through neovascularization and inflammation in atheromatous plaques (Inoue et al, 1998;Celletti et al, 2001). Some studies have shown that expression of VEGF and nerve growth factor are significantly higher in degenerative disc with no herniation compared with herniated disc, and angiogenesis is related to the presence of nerve fiber ingrowth into degenerative IVD and the appearance of discogenic low back pain (Freemont et al, 1997(Freemont et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-RFLP assay was performed to analyze these 3 SNPs. The primers and PCR conditions for the determination of eNOS SNP have been previously described (Inoue et al, 1998).…”
Section: Genotypingmentioning
confidence: 99%